PRINCIPLES OF DEVELOPMENT OF PSYCHOLOGICAL COMPETENCE OF LEADING EMPLOYEES - Gulavza Ergashevna Gazibekova (Web of Journals Publishing, 2024)
Increasing the managerial competencies of leaders implementing reforms, which are the basis for the development of a new Uzbekistan, is the basis for training suitable leaders. Two important tasks are focused in the development of management competencies of management personnel - the development of human capital strategically and the formation of knowledge and skills in accordance with the requirements of a market economy - tactically. In this regard, management competencies became the dominant concept in the theory of strategic management in the 90s of the twentieth century, and it was important to provide for the formation of competitive advantages based on the development of management competencies among management personnel. Therefore, the main task of a leader is to serve people, to please them, and they deeply understand their responsibility and accountability, first of all, to their conscience, to the people who trust them, to the nation, to fulfill their assigned tasks . entrusted to them, they show diligence and help others, must also call for dedication and work. Therefore, managers are faced with important tasks to achieve these goals, and there are also tasks to further expand research in this direction. Therefore, this article reveals the scientific and theoretical foundations of the psychological competence of a leader.
Keywords: Leadership personality, management psychology, personnel competence, professional competence, methodological competence, socio-psychological competence, communicative competence, managerial potential, resource concept, civil servants.